Tailoring thermal properties and fiber morphology in PVA nanofibers via addition of hydrothermally synthesized strontium oxide nanoparticles - Kok, Mediha; Tatar, Cengiz; Oner, Ecem Ozen (De Gruyter Poland Sp Z O O, 2026)
In this work, poly(vinyl alcohol) (PVA) nanofiber composites reinforced with hydrothermally synthesized strontium oxide (SrO) nanoparticles were fabricated via electrospinning to obtain thermally enhanced and functionally adjustable nanofibrous structures. The structural and interfacial interactions were examined by FTIR and XRD, revealing coordination bonding between Sr2+ ions and PVA hydroxyl groups, accompanied by partial suppression of PVA crystallinity and the emergence of crystalline SrO phases. Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) analyses demonstrated a notable enhancement in thermal stability, attributed to the barrier effect of SrO nanoparticles restricting polymer chain mobility. Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) observations showed a progressive reduction in fiber diameter and increased surface roughness with increasing SrO loading, while excessive filler contents led to nanoparticle agglomeration. PVA/SrO composites containing 5-10 wt% SrO exhibited an optimal balance between morphological continuity and thermal performance.
Keywords: poly(vinyl alcohol) (PVA); strontium oxide (SrO) nanoparticles; nanocomposite fibers